PEMBINAAN KELOMPOK INFORMASI MASYARAKAT (KIM) DALAM MENDUKUNG KELANCARAN PELAYANAN PUBLIK DI DESA LAMATTI RIAJA KECAMATA BULUPODDO KABUPATEN SINJAI - Sandi; Hardian, Dafyar Eliadi; Mulyadi, Edi (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2025)
This study aims to analyze the development of Community Information Groups (KIM) in supporting public services in Lamatti Riaja Village, Sinjai Regency. The research focuses on two aspects: KIM development, which includes aspects of direction, motivation, supervision, and coordination, and the supporting and inhibiting factors that influence the effectiveness of this development. This study used a qualitative approach, collecting data through in-depth interviews, observation, and documentation with six key informants from the village government, KIM administrators, and other relevant parties. The results indicate that KIM development still faces several obstacles. The direction provided by the village government and the Communication and Information Agency is largely general in nature, thus lacking clear technical guidance. Motivation of KIM members is also low due to the lack of incentives and rewards. Supervision of KIM performance is limited to annual reports without ongoing routine monitoring. Meanwhile, coordination between stakeholders has not been optimal, resulting in delays in the flow of information to the public. On the other hand, several supporting factors strengthen KIM's position, including formal regulations in the form of the Sinjai Regent's Regulation on KIM, support from the village government, and opportunities offered by developments in information technology. However, inhibiting factors are also significant, such as low public digital literacy, limited human resource competency within KIM, weak coordination, and minimal incentives and rewards. Therefore, it can be concluded that KIM's success in supporting public services depends heavily on targeted, intensive, and continuous development. Strengthening human resource capacity, providing motivation through incentives, optimizing the use of digital technology, and more effective cross-sector coordination are important strategies that need to be implemented to ensure KIM can optimally carry out its functions. Keywords: Development, KIM, Public Services, Direction, Motivation, Supervision, Coordination.